Macroeconomic and financial determinants of green growth: an empirical investigation on BRICS-T countries - ARZOVA, SABRİ BURAK (My University, 2023)
Purpose: The purposes of this study are to contribute to the limited green growth (GG) literature in emerging markets, to analyze GG from a financial economy perspective and to determine the contribution of financial development and innovation to GG in Brazil, Russian Federation, India, China and South Africa and Türkiye (BRICS-T). BRICS-T countries significantly impact the world population, international politics, energy resources and economy. In addition, BRICS-T countries are one of the leading countries in the world with their sustainability efforts. Investigating the GG model in these countries may contribute to structuring emerging economies around the principles of GG and advancing global green transformation efforts. Design/methodology/approach: The authors applied panel data analysis from 2001 to 2019. GG is economic growth free from environmental depletion in the model. National income, personnel expenditure and foreign direct investments are macroeconomic variables. These variables measure economic development and promote economic and social progress, which is essential for GG. Capital accumulation and innovation are essential tools in GG transformation. Therefore, financial development and patent applications represent the moderating variables. The authors estimate the fixed effect model with Parks-Kmenta robust. Findings: Empirical results show that national income growth and foreign direct investments positively affect GG. Personnel expenditure negatively affects GG. On the contrary, financial development and patent growth have little moderating role. Originality/value: This study contributes to the literature on creating a GG model in emerging countries. The study is original in its model and sample.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Social Sciences and Humanities; Sociology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; ÇEVRE ÇALIŞMALARI; Life Sciences (LIFE); Social Sciences (SOC); MOLECULAR BIOLOGY & GENETICS; SOCIAL SCIENCES, GENERAL; BIOCHEMISTRY & MOLECULAR BIOLOGY; ENVIRONMENTAL STUDIES; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Yönetim, İzleme, Politika ve Hukuk; Fizik Bilimleri; General Biochemistry, Genetics and Molecular Biology; Management, Monitoring, Policy and Law; Physical Sciences; Economic determination of green growth; Financial development; Green growth; Sustainability